THE H10N3 INFLUENZA STRAIN: A CANDIDATE FOR THE NEXT PANDEMIC? - Monawwer, Syed Abdullah; Taufiq, Haris; Muneeb, Muhammed; Meah, Khubaib Muhammad Shamim (Journal of Ayub Medical College Abbottabad, 2022)
The COVID-19 pandemic has devastated the world's demographics. As of December 2021, the virus has claimed over 5.3 million lives and has caused high morbidity across the globe. As the recently developed vaccines provided some hope of relief, a recent development is a cause of further distress as the first human case of the rare avian influenza A (H10N3) virus was detected in a 41-year-old man from the Zhenjiang province, China. The man has since recovered and has been discharged. The avian influenza A(H10N3) virus belongs to the Orthomyxoviridae family which mainly causes respiratory symptoms with primary viral pneumonia being the main cause of mortality. Genetic analysis on the patient's bronchoalveolar lavage confirmed the presence of the H10N3 subtype and that the virus had gone under reassortment with multiple other avian strains. Although the virus is deemed incapable of human-to-human spread, further mutations in its genome may allow it to do so. This would lead to a large-scale outbreak and reap calamitous outcomes, causing high morbidity and mortality. Moreover, this would further disrupt daily activities, spiking mental health issues. As the global economy tries to recover from the destitution caused by Covid-19, another pandemic would cripple the already struggling businesses and cause a further loss of livelihood. This calls for increased surveillance in poultry and an upscale in research for vaccine development as well as a contingency plan in case a large-scale outbreak was to occur.